2019
DOI: 10.1063/1.5117335
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the Langevin horn: Transducer arrays for the acoustic levitation of liquid drops

Abstract: The acoustic levitation of liquid drops has been a key phenomenon for more than 40 years, driven partly by the ability to mimic a microgravity environment. It has seen more than 700 research articles published in this time and has seen a recent resurgence in the past 5 years thanks to low cost developments. As well as investigating the basic physics of levitated drops, acoustic levitation has been touted for container free delivery of samples to a variety of measurements systems, most notably in various spectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 50 publications
0
34
0
2
Order By: Relevance
“…7(a) shows the evaporation constant up to the precipitation time (complete evaporation of water) for each sample. The horizontal axis represents time, and the vertical axis represents the evaporation constant with the different initial droplet size and concentration obtained from eqn (7). For the effect of the initial droplet diameter of the salt solution, it was conrmed that the evaporation constant decreased as the initial droplet size increased for each concentration.…”
Section: Time Estimation For Complete Salt Precipitationmentioning
confidence: 99%
See 2 more Smart Citations
“…7(a) shows the evaporation constant up to the precipitation time (complete evaporation of water) for each sample. The horizontal axis represents time, and the vertical axis represents the evaporation constant with the different initial droplet size and concentration obtained from eqn (7). For the effect of the initial droplet diameter of the salt solution, it was conrmed that the evaporation constant decreased as the initial droplet size increased for each concentration.…”
Section: Time Estimation For Complete Salt Precipitationmentioning
confidence: 99%
“…The theoretical predictions were in good agreement with the experimental results. It could be concluded that the precipitation time, when the water component completely evaporates, can be predicted using eqn (7) and (8).…”
Section: Time Estimation For Complete Salt Precipitationmentioning
confidence: 99%
See 1 more Smart Citation
“…The acoustic levitation [1,2] of droplets is a promising tool for contactless fluid manipulation for lab-on-a-drop applications [3][4][5][6][7][8] by achieving droplet levitation, transportation, coalescence, mixing, separation, evaporation, and extraction in a single operation. Through acoustic levitation, a sample can be suspended using the acoustic radiation force acting on the object [9]. This method enables contactless treatment to avoid the contamination, absorption, and heterogeneous nucleation through the wall effect [2].…”
Section: Introductionmentioning
confidence: 99%
“…The acoustic levitation [1,2] of droplets is a promising tool for contactless fluid manipulation for lab-on-a-drop applications [3][4][5][6][7][8] by achieving droplet levitation, transportation, coalescence, mixing, separation, evaporation, and extraction in a single operation. Through acoustic levitation, a sample can be suspended using the acoustic radiation force acting on the object [9]. This method enables contact-free treatment such as contamination, absorption, and heterogeneous nucleation through the wall effect [2].…”
Section: Introductionmentioning
confidence: 99%